Zakat and Islamic Bank Financial Performance: Do Third Party Funds Play an Important Role? - Anis Dariati; Dama Mustika (Journal of Business Management and Islamic Banking, 2025)
Research Aims: Using third-party money as a moderating variable, the study intends to investigate how zakat affects Indonesian Islamic banking performance Methodology: The research sample consisted of 16 Islamic banks selected using the total sampling method based on the availability of annual financial report data at the financial services authority using smartpls 3.0 and structural equation modeling, the data analysis method was executed. Research Findings: The findings demonstrate that zakat improves Islamic financial performance. This finding supports the theory that optimal zakat fund collection can increase customer trust in Islamic banks. In addition, third party funds strengthen the connection between financial achievement and zakat. This finding is also consistent with the premise that the allocation of third-party finances and funding is positively impacted by optimal zakat and growing public trust. Theoretical Contribution: By enhancing knowledge of the impact of zakat and the function of third-party funds in enhancing the financial performance of Islamic banks, this work makes a substantial theoretical contribution. Research limitation and implication: This study is limited to the sample and use of secondary data, which needs to be considered in interpreting the research findings. The implications of this study are useful for Islamic banks and further researchers to create more thorough research and more efficient tactics.